Ethernet Based Optical Tomography System - Abdul Rahim, Ruzairi; Goh, Chiew Loon; Chan, Kok San (Penerbit UTM Press, 2005)

(untitled)
Optical Tomography Is One Of The Methods Of Process Tomography, Which Is Less Expensive, Has A Better Dynamic Response And Is More Portable For Routine Use In Process Plant Than Other Radiation-Based Tomographic Methods. The Main Objective Of This Research Is To Optimize The Performance Of The Optical Sensors By Increasing The Data Transfer Rate From Hardware To Personal Computer.